Hubungan Kebiasaan Sarapan dan Aktivitas Fisik dengan Status Gizi Remaja di SMP Negeri 6 Kupang - Rani Riwu; Utma Aspatria; Rut Rosina Riwu (Yayasan Literasi Sains Indonesia, 2024)
Nutritional status is a condition or measure of a person's body condition caused by a balance between intake of nutrients from food and nutritional needs. Adolescents are one of the groups at risk for nutritional problems. Nutritional problems in adolescents can be caused by food intake, physical activity, economy, social, and culture. This research was conducted at SMP Negeri 6 Kupang, Alak Sub-district, Kupang City. This research was purposed to analyze the correlation between breakfast habits and physical activity with the nutritional status of adolescents at SMP Negeri 6 Kupang (state junior high school). This research is a correlational analysis and the design approach is a cross-sectional study, with a sample of 100 students which consist of students in grades VII, VIII and IX. The instruments used in this research were nutritional status measurement sheet, breakfast habit questionnaire, PAL (Physical Activity Level), and antropometric measurement (body weight and height). The results of research using the Spearman's Rank Correlation Test show that there is a significant relationship between breakfast habits (p = 0.000 < 0.05) and nutritional status of adolescents and has a level correlation coefficient of 0.594 or sufficient. Meanwhile, there is no significant relationship between physical activity and nutritional status (p=0.940 > 0.05) and has a correlation coefficient of -0.008 or very weak. In conclusion, that breakfast habits are related to the nutritional status of adolescents, where as physical activity is not related to nutritional status of adolescents.